Population biology of the Florida Manatee - O?Shea, Thomas J.; Ackerman, Bruce B.; Percival, H. Franklin (U.S. Dept. of the Interior, National Biological Service, 1995)
Proceedings of a workshop held at the Austin Cary Forest of the University of Florida, Feb. 4-6, 1992.